Islanding Detection in a Distribution System with Modified DG Interface Controller - Abbineni Sai Subhadra; P. Linga Reddy; Shailesh B. Modi (Institute of Advanced Engineering and Science, 2017)
Islanding detection of Distributed Generation (DG) is considered as one of the most important aspects when interconnecting DGs to the distribution system. It was the crucial problem in distributed generation. This detection phenomenon having a great importance. These detection methods are divided into active and passive islanding detection. These two methods are based on changing in parameters such as frequency, voltage and current harmonics. But these methods have some challenges such as reduction in power quality and large Non Detection Zone (NDZ). In this paper, the proposed method is change of Total Harmonic Distortion (THD) will be studied for islanding detection diagnosis. The studied system was considered by following the standard IEEE-1547 and UL-1741. The system was simulated using MATLAB/ SIMULINK.